2020
DOI: 10.1177/1932296820939626
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Diabetes Meeting 2020

Abstract: Patients with diabetes may experience adverse outcomes related to their glycemic control when hospitalized. Continuous glucose monitoring systems, insulin-dosing software, enhancements to the electronic health record, and other medical technologies are now available to improve hospital care. Because of these developments, new approaches are needed to incorporate evolving treatments into routine care. With the goal of educating healthcare professionals on the most recent practices and research for managing diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Inpatient diabetes management teams may not be available at other institutions; caution should be taken in extrapolating these results. 25 In a large academic medical center, a quality improvement project concluded that with proper medication safety features in place there are major benefits of using insulin pens in the inpatient setting. 26 In a pilot study conducted at the University of California, San Francisco Medical Center, it was determined that using the EHR to directly integrate patient safety improvements regarding insulin pens offered an opportunity to enhance patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient diabetes management teams may not be available at other institutions; caution should be taken in extrapolating these results. 25 In a large academic medical center, a quality improvement project concluded that with proper medication safety features in place there are major benefits of using insulin pens in the inpatient setting. 26 In a pilot study conducted at the University of California, San Francisco Medical Center, it was determined that using the EHR to directly integrate patient safety improvements regarding insulin pens offered an opportunity to enhance patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate priorities include appropriate fluid administration, electrolyte balance, and blood glucose management. Insulin is the pharmacologic agent of choice to manage blood glucose in hospitalized patients requiring glycemic management due to its quick onset and ease of adjustment based on dynamic individual needs [ 53 ]. Structured insulin order sets should be implemented to increase efficiency and decrease dosing errors.…”
Section: Postoperative Periodmentioning
confidence: 99%
“…Hospital diabetes management teams vary by institutions based on needs and resources. The increase in the diabetes population seeking care, advancement in diabetes therapies and technology, potential for improved outcomes, and cost savings are a few of the factors that support implementation of a diabetes management program [ 53 ]. Involvement of a diabetes service in select patients from the preoperative or admission phase to discharge enhances the entire perioperative experience and associated outcomes such as length of stay, readmission, and mortality [ 56 ].…”
Section: Postoperative Periodmentioning
confidence: 99%
“…Or perhaps, endocrinologists may not have enough business/financial skills to put together a business plan? 34,45 Could there be a financial explanation? Endocrine hospitalists may not be able to generate enough revenue through billings to cover the entire cost of salaries and benefits, even if the impact on quality metrics is significant.…”
Section: Challengesmentioning
confidence: 99%